The Beauty Standard Issue in Poster of Citra Hand and Body Lotion - Agnes Emmilia Eka Rosanti (The English Department, Faculty of Humanities & Creative Industries, Petra Christian University, 2024)
Each of the countries of the world has its own beauty standard, including body image. Body image here includes the color and the style of the hair, the eyes shape and color, the shape of the face, and the body shape. Often, the agency hires a model, an actor, or an actress who has a good look and body image to do a photo and video shoot for the commercial, poster, magazine cover, and other media to make the media interesting, to persuade the customers to buy the product, and to show the beauty standard to the readers. Unfortunately, some readers feel so insecure because they do not have the same good body image as the model on the media. In Indonesia, there is a commercial that shows a beauty of woman comes from her white skin and that is Citra hand and Body Lotion. Whereas the beauty of a woman does not only come from her skin tone. Unfortunately, there are still Indonesian people who believe that woman must has white skin to fulfill the beauty standard. This analysis will use the poster of hand and body lotion product branded Citra as one of the media. This paper shows the analysis of the issue of the beauty standard of girl in a poster of Citra Hand and Body Lotion.